2008
DOI: 10.1017/s0022112008000530
|View full text |Cite
|
Sign up to set email alerts
|

Flow across microvessel walls through the endothelial surface glycocalyx and the interendothelial cleft

Abstract: A mathematical model is presented for steady fluid flow across microvessel walls through a serial pathway consisting of the endothelial surface glycocalyx and the intercellular cleft between adjacent endothelial cells, with junction strands and their discontinuous gaps. The three-dimensional flow through the pathway from the vessel lumen to the tissue space has been computed numerically based on a Brinkman equation with appropriate values of the Darcy permeability. The predicted values of the hydraulic conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The major molecular components of the glycocalyx are proteoglycans with their glycosaminoglycan side chains and glycoproteins (24). However, resent observations from autocorrelation imaging techniques have suggested a structural model for the glycocalyx, which is composed of bush-like clusters of core proteins (22,32). Based on these images, we model the glycocalyx as a fiber matrix characterized by a (Darcy) hydraulic permeability coefficient, K Pg, given by (32): (10) where af is the fiber radius (6 nm) and ⌬ is the spacing between fibers (20 nm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major molecular components of the glycocalyx are proteoglycans with their glycosaminoglycan side chains and glycoproteins (24). However, resent observations from autocorrelation imaging techniques have suggested a structural model for the glycocalyx, which is composed of bush-like clusters of core proteins (22,32). Based on these images, we model the glycocalyx as a fiber matrix characterized by a (Darcy) hydraulic permeability coefficient, K Pg, given by (32): (10) where af is the fiber radius (6 nm) and ⌬ is the spacing between fibers (20 nm).…”
Section: Methodsmentioning
confidence: 99%
“…The tight junctions form lines of contact between the adjacent cells and act as barrier for water and solute to flow within the cleft (22). The dominant pathway for water through tight junctions in clefts is large, infrequent, widely spaced breaks (22,32).…”
Section: Methodsmentioning
confidence: 99%
“…Note that the interfinger distance is 1 mm and the density of ADJs is 1 mm 22 [59 -61]. ADJs are located at 25% of the cleft depth or 250 nm from the apical surface [36,73]. The shape, location and distribution of ADJs in the cell -cell interface in this model are shown in figure 1d.…”
Section: Geometric Modelmentioning
confidence: 99%
“…The glycocalyx layer has been described as a mechanosensor and transducer of FSS on ECs [1,5,[25][26][27][28][29][30][31][32][33][34][35][36]. Theoretical models to describe the transmission of force from fluid flow to the surface of cells covered by glycocalyx have revealed & 2014 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing models of transport through the inter-endothelial clefts are based on continuum approaches. However, it was suggested that more suitable analyses should be based on the molecular nature of the fluid because of the sizes of the mean intermolecular distances (∼ 0.3 nm) and the cleft width (∼18 nm) (Sugihara-Seki et al 2008). The development of multiscale computational models (Praprotnik and Delle Site 2008), coupling, for example, the molecular structure of the glycocalyx with a continuum description of the flow, is highly suitable in this context.…”
Section: Models Of Vascular Transport and Angiogenesismentioning
confidence: 99%